Binary Opposition as the Manifestation of the Spirit of Meiji in Natsume SÅsekiâ€™s Kokoro - Christanda, Richard Ahadi Christanda; Rosiandani, Ni Luh Putu (Universitas Sanata Dharma, 2019)
Every period in history has its own unique identity. Meiji period in historical Japan is no exception to this, having its own identity called the spirit of Meiji. This research attempts to reveal this identity, which present in the story of Kokoro, by using binary opposition. Binary opposition allows comparing and examining contradicting elements. Since the spirit of Meiji is defined as having â€œtwo contradictory elementsâ€, therefore, binary opposition is suitable for revealing the spirit of Meiji.The goal of this research is to show how binary opposition constitutes as a crucial element to the unique identity of Meiji period, which is the spirit of Meiji. In order to achieve this, two research problems are used as guides. One is how story of Kokoro presents the binary oppositions and two is how the spirit of Meiji manifests in the binary oppositions.In this research, library research was conducted in order to collect the relevant data. It uses texts in both printed form and digital form. The primary source for the research is the novel Kokoro by NatsumeSÅseki while the secondary sources are taken from various books and articles.The first step in explaining the spirit of Meiji is to examine the binary oppositions within in the story. The binary oppositions itself are revealed through the characters and the setting of the story. Through these two elements, five binary oppositions are revealed. They are past against present, old against young, rural against urban, community against privacy, and family against individual. These binary oppositions are then compared to the situation in real-world Meiji period in order to validate whether they really are the spirit of Meiji or not. It is then, through this direct comparison, the binary oppositions are found mirroring the situation in the real Meiji period. Therefore, it can be concluded that binary opposition is the manifestation of the identity of Meiji period, which is the spirit of Meiji.